Getting globalization right: the dilemmas of inequality - Tulchin, Joseph S.(ed.); Bland, Gary (ed.) (New Delhi Viva, 2007)
Getting Globalization Right explores political and economic changes in seven new democracies that have in common both a movement toward greater integration with the world economy and the challenges posed by persistent or even increasing domestic economic inequalities. The up-to-date, empirically rich case studies in the book cover the experiences of Brazil, Mexico, the Philippines, South Africa, South Korea, Spain, and Turkey. About Author: S Joseph S. Tulchin is former director of the Latin American Program at the Woodrow Wilson International Center for Scholars. Gary Bland is senior public policy and governance specialist at the Research Triangle Institute.
Keywords: Inequality